Occupational Dose Monitoring in Interventional Radiology Department at King Abdulaziz Medical City in Jeddah (KAMC-Jeddah) - Alzahrani, Hind; Alqahtani, Shouq; Alghamdi, Afnan; Almalki, Khalid; Subahi, Ahmad; Allabban, Muhammad (Journal of King Abdulaziz University: Engineering Sciences, 2024)
Background: Interventional Radiology (IR) is a relatively new and increasingly significant field in healthcare, offering minimally invasive procedures with shorter recovery times. However, as interventions become more complex and longer in duration, there is an increased risk of radiation exposure for medical staff. To address this, substantial efforts have been made to develop radiation protection measures and guidelines to minimize doses and ensure the safety of IR staff. Therefore, the purpose of this study is to measure the doses for IR workers and determine which workers had received the most radiation exposure, as well as dose map the areas in the IR department. Methods: The data were measured in the form of Equivalent doses using OSL dosimeters worn under lead apron. The methodology for collecting the data of workers radiation doses was based on the most common procedures during the two months of data collection, which included PICC Line, Nephrostomy, Angioplasty, IVC Filter, Av fistulagram, Embolization, Cerebral Angiogram, and Stent Placement. Results: The study showed that the highest OSL doses were recorded during Embolization and Angioplasty procedures, with median SDE values of (0.0040, 0.0026, 0.0021) (0.0033, 0.0021, 0.0017 mSv) for Radiologists, Technologists, and Nurses, respectively. This indicates that Radiologists received the highest radiation dose. Additionally, mapping the procedure room of the angiography suite revealed that areas No. 1 and 5 were the most exposed to radiation, while areas No. 6, 7, 8, and 9 showed no radiation exposure at all. Conclusion: A better understanding of the occupational dose in Interventional Radiology was made possible by myOSL dosimeter measurements. Furthermore, several recommendations have been suggested to lower the dose for workers and maximize radiation safety and protection in the IR department.